Surgical Management of Pediatric Urolithiasis: Descriptive Study from a Tertiary Care Center in Nepal - Guragain, Bipin; Phuyal, Anjit; Gyawali, Milan; Pandit, Durga; Parajuli, Purushottam; Pradhan, Manish M; Poudyal, Sujeet; Chapagain, Suman; Luitel, Bhojraj; Chalise, Pawan R; Sharma, Uttam K; Gyawali, Prem R (Journal of Institute of Medicine Nepal, 2023)
Introduction Urolithiasis is common in the pediatric population in low-resource countries but appropriate management is not available in all parts of the country. This study aimed to identify demographic parameters, clinical characteristics, and surgical management of pediatric urolithiasis in a tertiary care center in Nepal. Methods This is a retrospective and descriptive study of pediatric patients (≤18 years) who underwent surgical management of urolithiasis in the Department of Urology and Kidney Transplant Surgery, Tribhuvan University Teaching Hospital from January 2021 to December 2022. Results Total 64 patients with Male: Female= 1.78:1 and a mean age of 8.63±5.56 years presented mostly with pain abdomen (93.8%) followed by lower urinary tract symptoms (26.6%), hematuria (20.3%), and fever (14.1%). The mean number of calculi was 2.2 ± 1.47 and the mean size was 13.97±8.30mm. Most of the calculi (39.1%) were in the right system and 90.62% were in the upper tract. Only 15.62% of patients had calculi in the lower tract. Open surgeries were performed in only 10.93% and the rest were managed by minimally invasive procedures. Percutaneous nephrostomy tube insertion was done in 6 (9.37%) of patients and 1 (1.56%) underwent nephrectomy for nonfunctioning kidney. Conclusion Pediatric urolithiasis patients presented with pain abdomen, lower urinary tract symptoms, or hematuria. Surgical management has shifted from open surgeries in the past to minimally invasive surgeries at present.